Continuous gas-phase synthesis of core–shell nanoparticles via surface segregation. Issue 11 (20th April 2021) - Snellman, Markus; Eom, Namsoon; Ek, Martin; Messing, Maria E.; Deppert, Knut
Abstract : A continuous gas-phase synthesis method is employed to generate Cu@Ag core–shell nanoparticles with uniform size, composition, and bimetallic configuration. We discuss how the bimetallic morphology can also be tuned into a quasi-Janus structure. Abstract : Synthesis methods of highly functional core@shell nanoparticles with high throughput and high purity are in great demand for applications, including catalysis and optoelectronics. Traditionally chemical synthesis has been widely explored, but recently, gas-phase methods have attracted attention since such methods can provide a more flexible choice of materials and altogether avoid solvents. Here, we demonstrate that Cu@Ag core–shell nanoparticles with well-controlled size and compositional variance can be generated via surface segregation using spark ablation with an additional heating step, which is a continuous gas-phase process. The characterization of the nanoparticles reveals that the Cu–Ag agglomerates generated by spark ablation adopt core–shell or quasi-Janus structures depending on the compaction temperature used to transform the agglomerates into spherical particles. Molecular dynamics (MD) simulations verify that the structural evolution is caused by heat-induced surface segregation. With the incorporated heat treatment that acts as an annealing and equilibrium cooling step after the initial nucleation and growth processes in the spark ablation, the presented method is suitable for creating nanoparticles with both uniform size and composition and uniform bimetallic configuration. We confirm the compositional uniformity between particles by analyzing compositional variance of individual particles rather than presenting an ensemble-average of many particles. This gas-phase synthesis method can be employed for generating other bi- or multi-metallic nanoparticles with the predicted configuration of the structure from the surface energy and atomic size of the elements.